Faktor Risiko Kelainan Refraksi Pada Mahasiswa Baru Fakultas Kedokteran dan Ilmu Kesehatan Universitas Warmadewa Angkatan 2020 - Ni Wayan Winianti; Ni Nyoman Wulan Yuanitasari; Ni Wayan Sedani (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2022)
Refractive errors are the main visual impairment and being the second leading cause of blindness worldwide. Visual impairment due to refractive errors is a health problem that needs attention because it can reduce productivity and quality of life in the future. This study aims to gain knowledge about prevalence and analyze risk factors for refractive errors in new students of the Medical Study Program Faculty of Medicine Warmadewa University 2020th Generation. This research was conducted at the Faculty of Medicine Warmadewa University during December 2020 - February 2021. This research is an analytical study with a cross sectional design and has passed ethical clearance. Sampling was carried out in a simple random sampling with a total sample of 114 people. Data collection methods consist of questionnaire and visual examination using snellen chart and pinhole test. The results showed that the prevalence of refractive error among new medical students of the Faculty of Medicine and Health Sciences Warmadewa University 2020th Generation was 59,6%. The result showed that there is significant association between parental history (p value=0.000), reading distance (p value=0.021), reading time (p value=0.022), duration of phone used (p value=0.000), duration of computer used (p value=0.013), frequency of outdoor activities (p value=0.028) and duration of outdoor activity (p value=0.019) with refractive errors. The logistic regression test showed that parental history (p value = 0.002) had a 7.340 times risk of causing refractive errors and also duration of phone used â‰¥2 hours (p value=0.000) had a 16.407 times risk causing refractive errors.